2022
DOI: 10.1071/ah22123
|View full text |Cite
|
Sign up to set email alerts
|

Perceived benefits of accessing a children’s sensory garden in a healthcare setting

Abstract: Objectives This pilot study aimed to explore the perceived benefits of a new children’s sensory garden in a healthcare centre in south-eastern Melbourne that provides specialised care, support and guidance to parents. Methods A mixed-method research design was employed in this study comprising a combination of quantitative (surveys) and qualitative (interviews) data collection methods. A total of 19 staff and 36 parents completed surveys relating to their experiences in the new garden. Results Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The experiences and preferences of these individuals across all studies were gathered using qualitative (n = 7), quantitative (n = 4), or mixed methods (n = 7). Examples of common qualitative methods include arts-based activities (25,30,31,34), observations (30,31,35,37,39,42), and interviews (25-28, 31, 34, 35, 42), whereas quantitative studies mostly used validated questionnaires (32,33,37) and surveys (26,27,29,36,37,(39)(40)(41)(42). Two thirds of the reviewed studies (n = 12) reported on specific types of play spaces in hospital settings, including gardens (n = 7), designated play or recreational rooms (n = 4), and playgrounds (n = 1).…”
Section: Collating Summarizing and Reporting The Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiences and preferences of these individuals across all studies were gathered using qualitative (n = 7), quantitative (n = 4), or mixed methods (n = 7). Examples of common qualitative methods include arts-based activities (25,30,31,34), observations (30,31,35,37,39,42), and interviews (25-28, 31, 34, 35, 42), whereas quantitative studies mostly used validated questionnaires (32,33,37) and surveys (26,27,29,36,37,(39)(40)(41)(42). Two thirds of the reviewed studies (n = 12) reported on specific types of play spaces in hospital settings, including gardens (n = 7), designated play or recreational rooms (n = 4), and playgrounds (n = 1).…”
Section: Collating Summarizing and Reporting The Resultsmentioning
confidence: 99%
“…The experiences and preferences of these individuals across all studies were gathered using qualitative ( n = 7), quantitative ( n = 4), or mixed methods ( n = 7). Examples of common qualitative methods include arts-based activities ( 25 , 30 , 31 , 34 ), observations ( 30 , 31 , 35 , 37 , 39 , 42 ), and interviews ( 25 28 , 31 , 34 , 35 , 42 ), whereas quantitative studies mostly used validated questionnaires ( 32 , 33 , 37 ) and surveys ( 26 , 27 , 29 , 36 , 37 , 39 42 ).…”
Section: Resultsmentioning
confidence: 99%